The challenges of implementing world class petroleum fuels specifications in developing countries - Mkwanazi, Samson (My University, 2011)
Petroleum fuels, mostly petrol and diesel, power automobiles that are indispensable as modern means of transport. Worldwide scientific research has shown that products of combustion from petroleum fuels cause numerous health problems and environmental damage. The international community now believe the solution lies in the implementing of new petroleum fuels specifications to reduce harmful vehicle emissions and make tail piece devices fitted in new vehicles usable. In having to implement the new petroleum fuels specifications, developing countries encounter challenges that are economical, social, technological and infrastructural in nature. This research sought experiences and understanding of South Africa by carrying out in-depth interviews with expert respondents that represented most stakeholders. The findings highlight the need for active role and proper planning by government. Developing countries should do cost and benefit analysis, improve the transportation system, reduce very old and non-roadworthy vehicles, harness knowledge and resources, work within realistic time frames and consider local context.
MBA thesis - WBS
Keywords: Petroleum fuels; Developing countries